Cesium-131 Interstitial Brachytherapy for Recurrent Malignancies of Skull Base - Savard, Corey; Epps, Gregory; Ad, Voichita Bar; Curry, Joseph; Evans, James J.; Farrell, Christopher J.; Nyquist, Gurston; Luginbuhl, Adam (Journal of Neurological Surgery Reports, 2019)
Background Recurrent malignancy of the skull base poses a treatment challenge due to a lack of treatment options and potential for damage to surrounding structures.Methods Case report of two patients with recurrent nasopharyngeal carcinoma (NPC) of skull base previously treated with adjuvant chemoradiotherapy using intensity-modulated radiation therapy (IMRT).Results In both cases, the recurrent tumor was treated with endoscopic surgical resection and intraoperative cesium-131 (Cs-131) interstitial brachytherapy (IBT). Total dose delivered to tumor bed was 57 and 60 Gy, respectively. With a half- life of 9 days, the majority of the radiation dose had been delivered within the first 40 days following implant and there have been no treatment-related complications reported.Conclusion Intraoperative Cs-131 IBT is a feasible adjuvant treatment option for patients with recurrent malignancies of the skull base. These are the first known cases of Cs-131 IBT used for recurrent NPC.
Keywords: cesium-131; interstitial; brachytherapy; nasopharyngeal carcinoma; recurrent